The neurobiological basis of affect is consistent with psychological construction theory and shares a common neural basis across emotional categories - Doğa Gündem; Jure Potočnik; François-Laurent De Winter; Amal El Kaddouri; Daphne Stam; Ronald Peeters; Louise Emsell; Stefan Sunaert; Lukas Van Oudenhove; Mathieu Vandenbulcke; Lisa Feldman Barrett; Jan Van den Stock (Communications Biology, 2022)
Analysis of fMRI recordings from an autobiographical memory recall tasks suggests that neural activation during emotional experiences can be better predicted by psychological construction theory, rather than classic basic emotions theory.